Revolutionizing medical research with artificial intelligence: opportunities, challenges, and strategies: a review - Mohammed Abudasir, Anas; Saeed, Abdullah; Bin Saeed, Abdulrahman; Mohammed Abudasir, Abdulaziz; Yahya Alhayani, Ali; Saeed Aldlham, Khalid; E. Mustafa Ahmed, Ghassan; Abdullah Alqahtani, Razan (International Journal of Research in Medical Sciences, 2025)
This article provides an in-depth exploration of the growing role of artificial intelligence (AI) in medical research, identifying potential applications, key case studies, challenges, strategies for implementation, and future perspectives. AI presents immense opportunities to revolutionize medical research, offering tools for efficient data analysis, accurate prediction of outcomes, and enhanced research efficiency. Specific areas such as genomics, drug discovery, clinical trials, and epidemiology can especially benefit from AI's application, as evidenced by various case studies. However, the journey towards full AI integration in medical research is not without obstacles. Data privacy issues, the necessity for specialized knowledge, rigorous validation of AI models, and algorithm interpretability emerge as significant hurdles. Moreover, ethical considerations, such as the risk of bias in AI algorithms, add another layer of complexity. Realizing these challenges demands ongoing innovation, research, and collaboration across various stakeholders. AI's intersection with medical research heralds a new era of potential scientific discoveries and improved patient outcomes. The article calls for a joint effort from researchers, practitioners, and policymakers to embrace this potential, navigate the challenges, and shape a future where AI serves as an invaluable tool in the pursuit of improved healthcare for all.